Increased Induction of Apoptosis by a Sendai Virus Mutant Is Associated with Attenuation of Mouse Pathogenicity - Itoh, Masae (American Society for Microbiology, 1998)
An avirulent mutant of Sendai virus, Ohita-MVC11 (MVC11), was generated from a highly virulent field strain, Ohita-M1 (M1), through successive passages in LLC-MK(2) cell cultures (M. Itoh, Y. Isegawa, H. Hotta, and M. Homma, J. Gen. Virol. 78:3207-3215, 1997). In LLC-MK(2) cells, MVC11 induced a high degree of apoptotic cell death that was demonstrated by chromatin condensation of the nucleus and DNA fragmentation, and production of MVC11 declined markedly after prolonged culture. On the other hand, M1 did not induce prominent apoptosis and maintained high virus titers. In primary mouse pulmonary epithelial cell cultures, M1 replicated rather slowly to reach maximum level of virus production at 3 days postinfection, and high levels of virus production were maintained thereafter without causing apoptosis. In contrast, MVC11, which produced 20 times more progeny virus than M1 at 1 day postinfection, induced a high degree of apoptotic cell death before the virus replication cycle was completed. Accordingly, the production of progeny virus was strongly inhibited thereafter. In the lungs of mice infected with MVC11, virus antigens and signals of DNA fragmentation detected by the in situ terminal deoxynucleotidyltransferase-mediated dUTP nick end-labeling technique colocalized in bronchial epithelial cells, clearly demonstrating that infection by MVC11 triggered apoptosis in vivo as well as in vitro. These results suggest the possibility that induction of apoptosis by MVC11 plays an important role in attenuation of mouse pathogenicity by restricting progeny virus production in the lung. The C protein was shown to have the capacity to induce apoptosis, and the increased level of the C protein in MVC11-infected cells was considered to account partly, if not entirely, for the induction of apoptosis.